(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. One of the frequent causes of poor vision in children is amblyopia which is encountered in 1–2 % of all children’s population. Principal causes of decrease in sight in children with congenital myopia are besides high myopic refractions, this or that degree of undevelopement of the visual analyzer. The diagnosis in this pathology is complicated, as complicated congenital myopia and undevelopement of the visual analyzer are often identified with amblyopia. Purpose. To compare visual functions in children with amblyopia and with congenital myopia of the same refraction. Material and methods. 93 children (186 eyes) at the age from 5 to 18 were supervised. Children with myopia of the same age with the same refraction have made a group of 36 (72 eyes). All carried out ophthalmologic investigations included evaluation of vision without and with correction, refractometry, skiascopy, in conditions of cycloplegia, determination of reserves of accommodation, echobiometry of visual axes, ophthalmoscopy, biomicroscopy. The condition of the visual analyzer was estimated by color thresholds by Rabkin’s tables, electrosensitivity threshold by phosphen, by critical frequency of disappearance of flashings by phosphen. Binocular functions were also investigated: binocular vision by color test, stereoacuity by stereograms (Lang’s test II) and time of occurrence of stereoeffect. Results. The comparative analysis has shown that in amblyopia with myopic refraction visual functions, such as «visual acuity with correction, color vision, stereoacuity are decreased more than in congenital myopia with the same refraction. It is established that in children with amblyopia color vision of all colors is significantly decreased, thresholds to dark blue color (7.5±4.8 in comparison with 3.2±3.3) in the absence of visible changes on the eye fundus. In children of both groups there was revealed a decrease in the function of stereovision in the presence of binocular vision. That is proved by high thresholds of stereovision by Lang’s test II (random-dot pictures).